APLIKASI WHISKER BOX PLOT TERHADAP KUALITAS AIR SUNGAI DI INDONESIA TAHUN 2007 - Dewi Ratnaningsih (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2009)
The aim of this report is in order to illustrates the overall river water quality in Indonesia in the form of whiskerbox plot graph. Whisker box plot is a convenient way of graphically depicting groups of numerical data troughfive numbers summaries: the smallest observation, lower quartile, median, upper quartile and largest observation.Median value is usefull tool to arrange the position of each river in the graph to indicated the level of river waterpollution compared with each other. River water data were collected from all over Indonesia including 33 riversof 30 provinces in 2007 and separated regarding to five regional areas including Jawa , Sumatera, Kalimantan, BaliNusraand Sumapua regional area. The result indicated that DO, BOD, COD, fenol, fecal coli and total coliformwere major pollution of river water in Indonesia. According to the median value of each parameter including BOD,COD, NO3, NH3, T-P, oil & grease and MBAS, Anafre river located in Papua Province were more polluted thanother rivers in Indonesia. Fecal coli and total coliform were also tend to be major pollution of the river locatedin dense population of Jawa regional area including Ciliwung river in Jakarta. Batu Merah and Batu Gajah riverlocated in Maluku Province were also tend to be high contaminated by fecal coli. Regarding to these condition itis necessary to manage river water quality in order to keep the river water quality suitable for creature or humanlife, since domestic, industrial, agricultural and animal husbandry waste have affected the river water quality